An Endophytic Bacterial Strain Isolated from Eucommia ulmoides Inhibits Southern Corn Leaf Blight - Ding, Ting; Su, Bo; Chen, Xiaojie; Xie, Shanshan; Gu, Shuangyue; Wang, Qi; Huang, Dayue; Jiang, Haiyang (Frontiers in Microbiology, 2017)
Bacillus subtilis DZSY21 isolated from the leaves of Eucommia ulmoides oliv. was labelled by antibiotic marker and found to effectively colonize the leaves of maize plant. Agar diffusion assays and biocontrol effect experiments showed that strain DZSY21 and its lipopeptides had antagonistic activity against Bipolaris maydis, as well as high biocontrol effects on southern corn leaf blight caused by B. maydis. Using MALDI-TOF-MS analysis, we detected the presence of antimicrobial surfactin A, surfactin B and fengycin in the strain DZSY21. Signaling pathways mediated by DZSY21 were analyzed by testing the expression of key plant genes involved in regulation of SA or JA/ET pathways, the defense-related genes PR1 and LOX were concurrently expressed in the leaves of DZSY21-treated plants; this corresponded to slight increase in the expression level of PDF1.2 and decreases in ERF gene transcription levels. The results indicated an induced systemic response that is dependent on the SA and JA pathways. Thus, we hypothesized that the strain DZSY21 inhibits Bipolaris maydis by producing antifungal lipopeptides and activating an induced systemic response through SA- and JA-dependent signaling pathways. This work describes a mechanism behind reduced disease severity in plants inoculated with the endophytic bacteria DZSY21.